Polycultural Resource of Professional Training of Future Social Teachers - Olha Gurenko (Pedagogical Discourse, 2012)
The essence of polycultural education of future social teachers are revealed in the article. On the basis of the analysis of educational programs of the direction of preparation «Social pedagogics», general and work programs the topics of educational disciplines are defined, problems of polycultural and training of future social teachers to activity in polycultural society are considered. The polycultural resource of disciplines of a variation part of the educational plan are shown.